PENGARUH INVESTASI, UPAH MINIMUM PROVINSI, DAN INFLASI TERHADAP ANGKA PENGANGGURAN DI INDONESIA TAHUN 2015-2019 - Raka Muhammad Ziddan; Sakti, Rachmad Kresna (Journal of Development Economic and Social Studies, 2022)
Unemployment is an economic problem that is very influential on the economy of a country. The number of labor force that continues to increase with the number of jobs and the intense competition to get a job is something that must be overcome by a country. This study is to analyze the effect of investment, provincial minimum wage, and inflation on the target figures in Indonesia in 2015-2019. The research method used is quantitative analysis method using panel data regression. The location of the research was carried out in 34 provinces in Indonesia. The model used is a random effect model with the results of the study that there is a negative and significant relationship between investment and movement, the provincial minimum wage has a positive and significant effect on the impact, and inflation has a positive and significant effect on the movement.